Nonlinear Numerical Model of Headed Shear Stud Anchors for Composite Open Web Steel Joists - Yanez-Cart, S; Guzman-Inostroza, C; Pina, J (TECHNO-PRESS, 2022)
Empirical relationships that capture the nonlinear behavior of headed steel shear stud anchors have been derived from standard push out tests, where the specimens are comprised of large wide flanged steel sections attached to flat concrete slabs via the anchors. However, many composite systems used in practice utilize much smaller steel members and/or steel decking as part of the slab system. Composite open web steel joist systems generally include both of these elements and consequently the nonlinear performance of the anchor is not accurately represented by existing models. In this paper, a new empirical relation is presented for open web steel joist systems based on experimental results from a modified push out test that more realistically represent a composite open web steel joist system. The methodology for obtaining the proposed nonlinear function where the response of the system is characterized by two parameters (alpha and beta) is presented. The two-step process for obtaining the two parameters is described and the empirical relation is calibrated with the experimental data. In comparison with existing expressions, the new proposal herein more accurately predicts the high initial stiffness of the system and overall nonlinear system performance.